Identification of Circular RNAs Circ_0005008 and Circ_0005198 in Plasma as Novel Biomarkers for New-Onset Rheumatoid Arthritis - Ouyang, Qingqing; Liu, Chixiang; Lu, Xiaoxi; Liang, Renge; Zhao, Jinjun; Yang, Min (Frontiers in Pharmacology, 2021)
The progression of autoimmune diseases is affected by the differential expression of circular RNAs (circRNAs). However, in the plasma from rheumatoid arthritis (RA), circRNAs have an uncertain role. Herein, microarray analysis was used to determine the plasma expression profile of circRNAs from new-onset patients with RA and healthy controls (HCs). CircRNA expression was verified using quantitative real-time reverse transcription PCR. The correlation between clinical variables and circRNA expression was assessed using Spearman’s correlation test. The diagnostic value of plasma circRNAs was evaluated using receiver operating characteristic (ROC) curves. Circ_0005008 and circ_0005198 were confirmed to be elevated significantly in plasma samples from new-onset patients with RA compared with those from HCs and from patients with systemic lupus erythematosus. Among these new-onset patients with RA, we found that the levels of circ_0005008 and circ_0005198 correlated positively with the severity of disease, including the rheumatoid factor, C-reactive protein, the erythrocyte sedimentation rate, and the disease activity score in 28 joints (DAS28). However, their expression levels did not correlate with anti-cyclic citrullinated peptide antibodies. Analysis using ROC curves implied that circ_0005008 and circ_0005198 have significant value in the diagnosis of RA. In addition, we found that compared with that in osteoarthritis fibroblast-like synoviocytes (OA-FLSs), circ_0005198 expression was enhanced in RA-FLSs and correlated positively with DAS28. The level of the miRNA target of circ_0005198, miR-4778-3p, was identified as significantly decreased in RA-FLSs, and the expression levels of circ_0005198 and miR-4778-3p correlated significantly and negatively. The results suggested that in new-onset patients with RA, plasma circ_0005008 and circ_0005198 levels are associated with disease activity and represent possible RA biomarkers.